Salt form, crystal form and preparation method of 5, 6-dihydrothieno [3, 4-h] quinazoline compound

CN119630674APending Publication Date: 2025-03-14SHANGHAI FOSUN PHARMA DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380058022.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-08
Filing Date
2023-08-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing PLK1 inhibitors have limited efficacy and poor pharmacokinetic properties in the treatment of colorectal cancer and other solid tumors, especially low response rates in patients with KRAS mutant subtypes.

Method used

Developed a salt form and crystal form of 5,6-dihydrothieno[3,4-h]quinazoline compounds, and improved the inhibitory effect on PLK1 and oral bioavailability by optimizing its structure and preparation method Specifically, it includes preparing compounds of different salt forms and crystal forms, and ensuring their stability and drug prospects through X-ray powder diffraction, differential scanning calorimetry, thermogravimetric analysis and other methods.

Benefits of technology

It has achieved effective inhibition of PLK1, improved pharmacokinetic properties and oral bioavailability, and has good stability and drug prospects, especially showing high efficacy in patients with KRAS mutation subtypes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630674A_ABST
    Figure CN119630674A_ABST
Patent Text Reader

Abstract

The invention discloses a salt form and a crystal form of a 5, 6-dihydrothieno [3, 4-h] quinazoline compound, a preparation method of the salt form and the crystal form, and application of the salt form and the crystal form in preparation of medicines for treating colorectal cancer and other solid tumors.
Need to check novelty before this filing date? Find Prior Art

Description

A salt form, crystal form and preparation method of a 5,6-dihydrothieno[3,4-h]quinazoline compound

[0001] This application claims the following priority

[0002] CN202210948349.2, application date: August 8, 2022. Technical Field

[0003] The present invention relates to a salt form and a crystal form of a 5,6-dihydrothieno[3,4-h]quinazoline compound and a preparation method thereof, as well as application of the salt form and the crystal form in preparing drugs for treating colorectal cancer and other solid tumors. Background Art

[0004] Polo-like kinases (PLKs) are a highly conserved class of serine / threonine protein kinases. They all possess a highly homologous serine / threonine kinase domain at their N-termini and a characteristic polobox domain (PBD) at their C-termini that regulates PLK activity and subcellular localization. The PLK family comprises a large number of members, with four isoforms in humans: PLK1, PLK2, PLK3, and PLK4. They all play crucial roles in regulating various phases of the cell cycle. Of these four family members, PLK1 is currently the most thoroughly studied. Therefore, PLK1 is a highly sought-after target in tumor diagnosis and treatment.

[0005] Cardiff Oncology (formerly Trovagene), under license from Nerviano, is developing onvansertib (PCM-075; NMS-P937; nms-1286937; NMS-937), a fumarate salt, as an oral PLK-1 inhibitor. Onvansertib is a potential oral cancer treatment for indications including metastatic colorectal cancer (mCRC), solid tumors, acute myeloid leukemia (AML), and metastatic castration-resistant prostate cancer. Onvansertib is a novel, highly selective PLK1 inhibitor, a potent therapeutic target overexpressed in most cancers.

[0006] Onvansertib (NMS-1286937) is a highly selective PLK1 inhibitor currently in clinical development, with a strong inhibitory effect on the PLK1 kinase protein. It is currently being studied in Phase I or Phase II clinical trials as a monotherapy for the treatment of recurrent small cell lung cancer (SCLC) and in combination with SOC for the treatment of solid tumors such as KRAS-mutant metastatic colorectal cancer (mCRC), metastatic pancreatic cancer (mPDAC), and metastatic castration-resistant prostate cancer (mCRPC). Compared with KRASG12C inhibitors, PLK1 inhibitors have a higher response rate in CRC patients and are effective against all KRAS mutation subtypes. CRC is the third most common malignancy after lung cancer and breast cancer, with a global market value of approximately US$25 billion in 2018. Therefore, it is possible to find highly active, highly selective, and metabolically stable small molecule PLK1 inhibitors for tumor treatment.

[0007] Summary of the Invention

[0008] The present invention provides succinate, fumarate, benzenesulfonate, sulfate, phosphate, maleate, L-tartrate, methanesulfonate, L-malate, hydrochloride, citrate and L-aspartate salts of the compound of formula (I):

[0009] In some embodiments of the present invention, the salt of the above compound is selected from:

[0010] wherein m, n, p, q, r, s, t, u, v, w, x, and y are each independently selected from 0.5 to 3.0.

[0011] In some embodiments of the present invention, the salt of the above-mentioned compound, wherein m, n, p, q, r, s, t, u, v, w, x and y are independently selected from 0.8 to 2.0.

[0012] In some embodiments of the present invention, the salt of the above compound, wherein m, n, p, q, r, s, t, u, v, w, x and y are independently selected from 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and 2.0.

[0013] In some embodiments of the present invention, the salt of the above compound, wherein m is 1.0, n is 1.0, p is 1.0, q is 1.0, r is 1.0, s is 1.0, t is 1.0, u is 1.0, v is 1.0, w is 1.0, x is 1.0, and y is 1.0.

[0014] In some embodiments of the present invention, the salt of the above-mentioned compound, wherein m, n, p, q, r, s, t, u, v, w, x and y are each independently selected from 1.0.

[0015] The present invention provides a crystalline form A of the compound of formula (I), characterized in that its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 12.661±0.200°, 19.637±0.200°,

[0016] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 19.637±0.200°, 23.281±0.200°, and 24.892±0.200°.

[0017] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 14.139±0.200°, 19.637±0.200°, 23.281±0.200°, 24.892±0.200°.

[0018] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 13.479±0.200°, 19.637±0.200°, 23.281±0.200°, 24.892±0.200°.

[0019] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 13.479±0.200°, 14.139±0.200°, 16.523±0.200°, 18.385±0.200°, 19.637±0.200°, 21.161±0.200°, 23.281±0.200°, 24.892±0.200°.

[0020] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 11.138±0.200°, 12.661±0.200°, 13.479±0.200°, 14.139±0. 200°, 15.175±0.200°, 16.523±0.200°, 18.385±0.200°, 19.637±0.200°, 21.161±0.200°, 22.159±0.200°, 23.281±0.200°, 24.892±0.200°, 26.582±0.200°.

[0021] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 19.637±0.200°, and / or 9.681±0.200°, and / or 11.138±0.200°, and / or 12.661±0.200°, and / or 13.479±0.200°, and / or 14.139±0.200°, and / or 15.175±0.200°, and / or 16.523±0.200°, and / or 18.385±0.200°, and / or 18.710±0.200°, and / or 19.904±0.200°, and / or 20.692±0.200°, and / or 21.161±0.200°, and / or 21.915±0.200°, and / or 22.159±0.200°, and / or 23.281±0.200°, and / or 24.892±0.200°, and / or 25.491±0.200°, and / or 26.582±0.200°, and / or 32.389±0.200°.

[0022] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 19.637±0.200°, and / or 9.681±0.200°, and / or 11.138±0.200°, and / or 12.661±0.200°, and / or 13.479±0.200°, and / or 14.139±0.200°, and / or 15.175±0.200°, and / or 16.523±0.200°, and / or 18.385±0.200°, and / or Or 18.710±0.200°, and / or 19.094±0.200°, and / or 19.904±0.200°, and / or 20.692±0.200°, and / or 21.161±0.200°, and / or 21.915±0.200°, and / or 22.159±0.200°, and / or 23.281±0.200°, and / or 23.630±0.200°, and / or 24.892±0.200°, and / or 25.491±0.200°, and / or 26.582±0.200°, and / or 32.389±0.200°.

[0023] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305°, 9.140°, 9.681°, 11.138°, 12.661°, 13.479°, 14.139°, 16.523°, 18.385°, 19.637°, 19.904°, 21.161°, 22.159°, 23.281°, 24.892°, and 26.582°.

[0024] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form A has characteristic diffraction peaks at the following 2θ angles: 6.305°, 9.140°, 9.681°, 11.138°, 12.661°, 13.479°, 14.139°, 15.175°, 16.523°, 18.385°, 18.710°, 19.094°, 19.637°, 19.904°, 20.692°, 21.161°, 21.915°, 22.159°, 23.281°, 23.630°, 24.892°, 25.491°, 26.582°, and 32.389°.

[0025] In some embodiments of the present invention, the XRPD pattern of the above-mentioned Form A is substantially as shown in Figure 1.

[0026] In some embodiments of the present invention, the XRPD pattern analysis data of the above-mentioned Form A is shown in Table 1:

[0027] Table 1. XRPD pattern analysis data of Form A

[0028] In some embodiments of the present invention, the differential scanning calorimetry curve of the above-mentioned crystal form A has an onset value of an endothermic peak at 222.64±3.0°C.

[0029] In some embodiments of the present invention, the DSC spectrum of the above-mentioned crystal form A is shown in Figure 2.

[0030] In some embodiments of the present invention, the thermogravimetric analysis curve of the above-mentioned crystal form A shows a weight loss of 1.220% at 242±3°C.

[0031] In some embodiments of the present invention, the TGA spectrum of the above-mentioned crystal form A is shown in Figure 3.

[0032] The present invention provides a crystalline form B of a compound of formula (II), wherein m is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, characterized in that its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.855±0.200°, 17.861±0.200°, 19.915±0.200°, 24.154±0.200°,

[0033] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned B crystal form has characteristic diffraction peaks at the following 2θ angles: 13.855±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, and 24.154±0.200°.

[0034] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned B crystal form has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 13.855±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 24.154±0.200°, 27.518±0.200°.

[0035] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned B crystal form has characteristic diffraction peaks at the following 2θ angles: 13.855±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 23.449±0.200°, 24.154±0.200°, 27.518±0.200°.

[0036] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form B has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 11.034±0.200°, 13.855±0.200°, 14.350°±0.200°, 16.116±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 21.157±0.200°, 24.154±0.200°, 27.518±0.200°.

[0037] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form B has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 11.034±0.200°, 13.855±0.200°, 16.116±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 21.157±0.200°, 23.449±0.200°, 24.154±0.200°, and 27.518±0.200°.

[0038] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form B has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 11.034±0.200°, 12.635±0.200°, 13.855±0.200°, 14.350±0.200°, 16.116±0.200°, 17.861±0 .200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 21.157±0.200°, 24.154±0.200°, 24.702±0.200°, 26.884±0.200°, 27.518±0.200°, 31.071±0.200°.

[0039] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form B has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 11.034±0.200°, 12.635±0.200°, 13.855±0.200°, 14.350±0.200°, 16.116±0.200°, 17.861±0 .200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 21.157±0.200°, 23.449±0.200°, 24.154±0.200°, 24.702±0.200°, 27.518±0.200°, 31.071±0.200°.

[0040] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form B has characteristic diffraction peaks at the following 2θ angles: 13.855±0.200°, 17.861±0.200°, and / or 7.333±0.200°, and / or 11.034±0.200°, and / or 12.635±0.200°, and / or 13.534±0.200°, and / or 14.350±0.200°, and / or 16.116±0.200°, and / or 17.483±0.200°, and / or 18.76 4±0.200°, and / or 19.658±0.200°, and / or 19.915±0.200°, and / or 20.651±0.200°, and / or 21.157±0.200°, and / or 23.449±0.200°, and / or 23.806±0.200°, and / or 24.154±0.200°, and / or 24.702±0.200°, and / or 26.884±0.200°, and / or 27.518±0.200°, and / or 31.071±0.200°.

[0041] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned B crystal form has characteristic diffraction peaks at the following 2θ angles: 7.333°, 11.034°, 13.534°, 13.855°, 14.350°, 16.116°, 17.483°, 17.861°, 18.764°, 19.915°, 20.651°, 21.157°, 23.449°, 23.806°, 24.154°, and 27.518°.

[0042] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned B crystal form has characteristic diffraction peaks at the following 2θ angles: 7.333°, 11.034°, 12.635°, 13.534°, 13.855°, 14.350°, 16.116°, 17.483°, 17.861°, 18.764°, 19.658°, 19.915°, 20.651°, 21.157°, 23.449°, 23.806°, 24.154°, 24.702°, 26.884°, 27.518°, and 31.071°.

[0043] In some embodiments of the present invention, the XRPD pattern of the above-mentioned Form B is substantially as shown in Figure 5.

[0044] In some embodiments of the present invention, the XRPD pattern analysis data of the above-mentioned Form B are shown in Table 2:

[0045] Table 2. XRPD pattern analysis data of Form B

[0046] In some embodiments of the present invention, the differential scanning calorimetry curve of the above-mentioned Form B has an onset value of an endothermic peak at 193.63±3.0°C.

[0047] In some embodiments of the present invention, the DSC spectrum of the above-mentioned Form B is shown in Figure 6.

[0048] In some embodiments of the present invention, the thermogravimetric analysis curve of the above-mentioned Form B shows a weight loss of 0.867% at 92±3°C.

[0049] In some embodiments of the present invention, the TGA spectrum of the above-mentioned B crystal form is shown in Figure 7.

[0050] In some embodiments of the present invention, m of the above-mentioned B crystal form is selected from 1.1.

[0051] The present invention provides a crystalline form C of a compound of formula (III), wherein n is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, characterized in that its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.637±0.200°, 14.138±0.200°, 17.076±0.200°, 24.866±0.200°,

[0052] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form C has characteristic diffraction peaks at the following 2θ angles: 11.412±0.200°, 13.637±0.200°, 14.138±0.200°, 17.076±0.200°, 19.310±0.200°, 23.654±0.200°, 24.214±0.200°, 24.866±0.200°.

[0053] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form C has characteristic diffraction peaks at the following 2θ angles: 11.412±0.200°, 13.637±0.200°, 14.138±0.200°, 15.555±0.200°, 17.076±0.200°, 18.016±0.200°, 18.907±0.200°, 19.310±0.200°, 20.811±0.200°, 23.654±0.200°, 24.214±0.200°, 24.866±0.200°.

[0054] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form C has characteristic diffraction peaks at the following 2θ angles: 13.637±0.200°, 17.076±0.200°, 24.866±0.200°, and / or 5.677±0.200°, and / or 7.086±0.200°, and / or 11.412±0.200°, and / or 11.627±0.200°, and / or 13.200±0.200°, and / or 13.429±0.200°, and / or 14.138±0.200°, and / or 14.499±0.200°, and / or 15.167±0.200°, and / or 15.555±0.200°, and / or 15.763±0.200°, and / or 17.272±0.200°, and / or 18.016±0.200°, and / or or 18.171±0.200°, and / or 18.614±0.200°, and / or 18.907±0.200°, and / or 19.310±0.200°, and / or 19.656±0.200°, and / or 20.016±0.200°, and / or 20.811±0.200°, and / or 21.765±0.200°, and / or 22.748±0.200°, and / or 23.443±0.200°, and / or 23.654±0.200°, and / or 23.880±0.200°, and / or 24.214±0.200°, and / or 24.577±0.200°, and / or 25.987±0.200°, and / or 26.493±0.200°, and / or 27.011±0.200°, and / or 27.537±0.200°.

[0055] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form C has characteristic diffraction peaks at the following 2θ angles: 11.412°, 13.637, 14.138°, 15.555°, 17.076°, 18.016°, 18.907°, 19.310°, 20.811°, 23.654°, 24.214°, and 24.866°.

[0056] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned crystal form C has characteristic diffraction peaks at the following 2θ angles: 5.677°, 7.086°, 11.412°, 11.627°, 13.200°, 13.429°, 13.637°, 14.138°, 14.499°, 15.167°, 15.555°, 15.763°, 17.076°, 17.272°, 18.0 16°, 18.171°, 18.614°, 18.907°, 19.310°, 19.656°, 20.016°, 20.811°, 21.765°, 22.748°, 23.443°, 23.654°, 23.880°, 24.214°, 24.577°, 24.866°, 25.987°, 26.493°, 27.011°, 27.537°.

[0057] In some embodiments of the present invention, the XRPD pattern of the above-mentioned Form C is substantially as shown in Figure 9.

[0058] In some embodiments of the present invention, the XRPD pattern analysis data of the above-mentioned Form C are shown in Table 3:

[0059] Table 3. XRPD pattern analysis data of Form C

[0060] In some embodiments of the present invention, the differential scanning calorimetry curve of the above-mentioned crystal form C has an endothermic peak at 237.14±3.0°C.

[0061] In some embodiments of the present invention, the DSC spectrum of the above-mentioned crystal form C is shown in Figure 10.

[0062] In some embodiments of the present invention, the thermogravimetric analysis curve of the above-mentioned crystal form C shows a weight loss of 0.469% at 100±3°C.

[0063] In some embodiments of the present invention, the TGA spectrum of the above-mentioned C crystal form is shown in Figure 11.

[0064] In some embodiments of the present invention, n of the above-mentioned C crystal form is selected from 1.0.

[0065] The present invention provides a crystalline form D of a compound of formula (IV), wherein p is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, characterized in that its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 16.420±0.200°, 18.965±0.200°,

[0066] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned D crystal form has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 10.922±0.200°, 13.238±0.200°, 16.420±0.200°, 18.965±0.200°, 20.400±0.200°, 24.069±0.200°.

[0067] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned D crystal form has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 10.922±0.200°, 11.644±0.200°, 13.238±0.200°, 16.420±0.200°, 17.596±0.200°, 18.965±0.200°, 19.390±0.200°, 20.400±0.200°, 21.416±0.200°, 24.069±0.200°.

[0068] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned D crystal form has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, and / or 10.922±0.200°, and / or 11.644±0.200°, and / or 13.238±0.200°, and / or 13.741±0.200°, and / or 16.420±0.200°, and / or 16.720±0.200°, and / or 17.596±0.200°, and / or 17.930±0.200°, and / or 18.965±0.200°, and / or 19.390±0.200°, and / or 20.400±0.200°, and / or 21.416±0.200°, and / or 22.630±0.200°, and / or 23.473±0.200°, and / or 24.069±0.200°, and / or 24.832±0.200°, and / or 26.587±0.200°, and / or 27.661±0.200°.

[0069] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned D crystal form has characteristic diffraction peaks at the following 2θ angles: 6.859°, 8.784°, 10.922°, 11.644°, 13.238°, 16.420°, 17.596°, 17.930°, 18.965°, 19.390°, 20.400°, and 24.069°.

[0070] In some embodiments of the present invention, the X-ray powder diffraction pattern of the above-mentioned D crystal form has characteristic diffraction peaks at the following 2θ angles: 6.859°, 8.784°, 10.922°, 11.644°, 13.238°, 13.741°, 16.420°, 16.720°, 17.596°, 17.930°, 18.965°, 19.390°, 20.400°, 21.416°, 22.630°, 23.473°, 24.069°, 24.832°, 26.587°, and 27.661°.

[0071] In some embodiments of the present invention, the XRPD pattern of the above-mentioned D crystal form is basically as shown in Figure 13.

[0072] In some embodiments of the present invention, the XRPD pattern analysis data of the above-mentioned D crystal form are shown in Table 4

[0073] Table 4. XRPD pattern analysis data of Form D

[0074] In some embodiments of the present invention, the differential scanning calorimetry curve of the above-mentioned D crystal form has an onset value of an endothermic peak at 240.70±3.0°C.

[0075] In some embodiments of the present invention, the DSC spectrum of the above-mentioned D crystal form is shown in Figure 14.

[0076] In some embodiments of the present invention, the thermogravimetric analysis curve of the above-mentioned D crystal form shows a weight loss of 0.295% at 120±3°C.

[0077] In some embodiments of the present invention, the TGA spectrum of the above-mentioned D crystal form is shown in Figure 15.

[0078] In some embodiments of the present invention, p of the above-mentioned D crystal form is selected from 0.9.

[0079] The present invention also provides the use of the above-mentioned salt form, crystal form A of the compound of formula (I), crystal form B of the compound of formula (II), crystal form C of the compound of formula (III) and crystal form D of the compound of formula (IV) in the preparation of drugs for treating solid tumors.

[0080] In some embodiments of the present invention, the above-mentioned drug for treating solid tumors is a drug for treating colorectal cancer.

[0081] Technical Effects

[0082] The crystal form of the present invention has good stability, good hygroscopicity, and good drug development prospects. The compound of the present invention has a good inhibitory effect on PLK1, good pharmacokinetic properties, and good oral bioavailability.

[0083] Definition and Description

[0084] Unless otherwise indicated, the following terms and phrases used herein are intended to have the following meanings. A particular phrase or term should not be construed as ambiguous or unclear unless specifically defined, but rather should be understood in accordance with its ordinary meaning. When a trade name appears herein, it is intended to refer to the corresponding commercial product or its active ingredient.

[0085] The intermediate compounds of the present invention can be prepared by a variety of synthetic methods well known to those skilled in the art, including the specific embodiments listed below, embodiments formed by combining them with other chemical synthesis methods, and equivalent replacement methods well known to those skilled in the art. Preferred embodiments include but are not limited to the examples of the present invention.

[0086] The chemical reactions of the present invention are carried out in suitable solvents that are compatible with the chemical transformations of the present invention and the reagents and materials required. To obtain the compounds of the present invention, it may sometimes be necessary for those skilled in the art to modify or select synthetic steps or reaction schemes based on existing embodiments.

[0087] The present invention will be described in detail below through examples, which are not intended to limit the present invention in any way.

[0088] All solvents used in the present invention were commercially available and used without further purification.

[0089] The present invention uses the following abbreviations: rt stands for room temperature; THF stands for tetrahydrofuran; NMP stands for N-methylpyrrolidone; MeSO3H stands for methanesulfonic acid; DME stands for ethylene glycol dimethyl ether; DCM stands for dichloromethane; Xphos stands for 2-dicyclohexylphosphino-2'4'6'-triisopropylbiphenyl; EtOAc stands for ethyl acetate; MeOH stands for methanol; acetone stands for acetone; 2-Me-THF stands for 2-methyltetrahydrofuran; and IPA stands for isopropyl alcohol.

[0090] Compounds are manually or The software named the commercially available compounds using the supplier's catalog name.

[0091] The powder X-ray diffractometer (XRPD) method of the present invention

[0092] Instrument model: Bruker D2 PHASER X-ray diffractometer

[0093] Test method: Approximately 5 to 10 mg of sample was used for XRPD analysis.

[0094] The detailed XRPD parameters are as follows:

[0095] Light pipe: Cu, kα,

[0096] Light tube voltage: 30kV, light tube current: 10mA

[0097] Divergence slit: 0.60mm

[0098] Detector slit: 0.075mm

[0099] Anti-scatter slit: 0mm

[0100] Scanning range: 3-40 degrees

[0101] Step size: 0.02 degrees

[0102] Each step dwell time: 0.2 seconds

[0103] Differential Scanning Calorimeter (DSC) method of the present invention

[0104] Instrument model: TA Instruments DSC 250 Differential Scanning Calorimeter

[0105] Test method: Weigh 1-3 mg of sample into a sample pan, accurately weigh, record the weight, and then pierce a hole in an aluminum crucible for testing. Heat at a rate of 10°C / min from 25°C to the final temperature.

[0106] Thermogravimetric analysis (TGA) method of the present invention

[0107] Instrument model: TA Instruments TGA 550 Thermogravimetric Analyzer

[0108] Test method: Take 2-5 mg of sample into the sample pan (Al2O3), test it in an open state, and heat it from 25℃ to the specified temperature at a heating rate of 10℃ / min.

[0109] Dynamic Vapor Sorption (DVS) method of the present invention

[0110] Instrument model: SMS DVS Intrinsic dynamic vapor adsorption instrument

[0111] Test conditions: Take a sample (10-30 mg) and place it in the DVS sample tray for testing.

[0112] The detailed DVS parameters are as follows:

[0113] Temperature: 25℃

[0114] Balance: dm / dt = 0.002% / min (minimum: 10 min, maximum: 180 min)

[0115] RH (%) test steps: 10% (90% RH-0% RH-90% RH), 5% (95% RH-90% RH and 90% RH-95% RH)

[0116] RH (%) test step range: 0% RH-95% RH-0% RH

[0117] The classification of moisture absorption evaluation is shown in Table 5:

[0118] Table 5. Hygroscopicity evaluation classification

[0119] Note: ΔW% indicates the weight gain of the test sample at 25±1℃ and 80±2%RH. BRIEF DESCRIPTION OF THE DRAWINGS

[0120] FIG1 is a Cu-Kα radiation XRPD spectrum of the crystalline form A of the compound of formula (I);

[0121] FIG2 is a DSC spectrum of the crystalline form A of compound of formula (I);

[0122] FIG3 is a TGA spectrum of the crystalline form A of compound of formula (I);

[0123] FIG4 is a DVS spectrum of the crystalline form A of compound of formula (I);

[0124] FIG5 is a Cu-Kα radiation XRPD spectrum of the crystalline form B of compound of formula (II);

[0125] FIG6 is a DSC spectrum of the crystalline form B of compound of formula (II);

[0126] FIG7 is a TGA spectrum of the crystalline form B of compound of formula (II);

[0127] FIG8 is a DVS spectrum of the crystalline form B of compound of formula (II);

[0128] FIG9 is a Cu-Kα radiation XRPD spectrum of the crystal form C of the compound of formula (III);

[0129] Figure 10 is a DSC spectrum of the crystalline form C of compound of formula (III);

[0130] Figure 11 is a TGA spectrum of the crystalline form C of compound of formula (III);

[0131] Figure 12 is a DVS spectrum of the crystalline form C of compound of formula (III);

[0132] FIG13 is a Cu-Kα radiation XRPD spectrum of the crystalline form D of the compound of formula (IV);

[0133] Figure 14 is a DSC spectrum of the crystalline form D of compound of formula (IV);

[0134] FIG15 is a TGA spectrum of the crystalline form D of the compound of formula (IV). DETAILED DESCRIPTION

[0135] The present invention is described in detail below by way of examples, but is not intended to limit the present invention in any way. While the present invention has been described in detail herein, and specific embodiments thereof have been disclosed, it will be apparent to those skilled in the art that various changes and modifications can be made to the specific embodiments of the present invention without departing from the spirit and scope of the present invention.

[0136] Example 1: Preparation of compound of formula (I)

[0137] Step 1: Synthesis of compound 1-2

[0138] Compound 1-1 (60 g) was dissolved in tetrahydrofuran (600 mL), and tert-butoxybis(dimethylamino)methane (77.35 g) was added at 20°C. After the addition, the temperature was raised to 80°C and the reaction mixture was reacted for 12 hours. The temperature was lowered to 20°C, water (200 mL) was added to the reaction mixture, and then the mixture was concentrated under reduced pressure. Water (400 mL) was added to the reaction mixture and stirred for 3 hours. The mixture was filtered, the solid was collected, and air-dried to obtain a crude product. 2-Methyltetrahydrofuran (160 mL) and methyl tert-butyl ether (480 mL) were added to the crude product, stirred at 20°C for 3 hours, filtered, the solid was collected, and the solid was dried under reduced pressure to obtain compound 1-2. LCMS: m / z (ESI) = 326.3 [M+H] + . 1 H NMR (400MHz, CDCl3) δ: 7.59 (s, 1H), 4.35-4.29 (m, 2H), 3.19-3.16 (t, 2H, J = 6.8Hz), 3.12 (s, 6H), 2.89-2.86 (t, 2H, J = 6.8Hz), 2.58 (s, 3H), 1.39-1.35 (t, 3H, J = 7.0Hz).

[0139] Step 2: Synthesis of Compounds 1-4

[0140] Compound 1-3 (78 g) was dissolved in dimethyl sulfoxide (640 mL), and compound 1-2 (80 g) was added. The temperature was raised to 110 ° C and the reaction was allowed to proceed for 48 hours. The temperature was lowered to 30 ° C, diluted with water (3 L), stirred for 0.5 hours, filtered, rinsed with water (200 mL), and the filter cake was collected. Acetonitrile (750 mL) was added to the filter cake and stirred at 50 ° C for 2 hours. The filter cake was filtered and rinsed with acetonitrile (200 mL). The filter cake was then added with acetonitrile (400 mL) and stirred at 25 ° C for 16 hours. The filter cake was filtered and rinsed with acetonitrile (80 mL). The filter cake was collected and dried under reduced pressure to obtain compound 1-4. LCMS: m / z (ESI) = 580.2 [M+H] + . 1 H NMR(400MHz,DMSO-d6)δ:8.55(s,1H),8.34(s,1H),7.49-7.46(m,1H),7.19-7.1 7(m,1H),6.73-6.71(m,1H),4.31-4.25(m,2H),3.32-3.15(m,6H),2.79-2.76(m 2H),2.57-2.44(m 7H),2.22(s,3H),1.32-1.28(m,3H).

[0141] Step 3: Synthesis of Compounds 1-5

[0142] Compound 1-4 (86.8 g) was dissolved in anhydrous tetrahydrofuran (520 mL), and a solution of lithium hydroxide monohydrate (18.9 g) in water (780 mL) was added to the system. Methanol (87 mL) was then added and the temperature was raised to 36.5°C for 16 hours. The reaction solution was concentrated under reduced pressure to remove the organic solvent to obtain a crude product. Water (780 mL) and 2-methyltetrahydrofuran (78 mL) were added to the crude product. The pH was adjusted to 7 with concentrated hydrochloric acid under stirring, and then to 6.5 with 1N dilute hydrochloric acid. The mixture was filtered and the filter cake was collected. Acetone (800 mL) was added to the filter cake, and the mixture was refluxed under stirring for 2 hours. The temperature was then lowered to 25°C and filtered. The mixture was rinsed with acetone (300 mL). The filter cake was collected and dried under reduced pressure to obtain compound 1-5. LCMS: m / z (ESI) = 552.0 [M+H] + . 1 H NMR(400MHz,DMSO-d6)δ:8.49(s,1H),8.32(s,1H),7.49-7.48(m,1H),6.74-6.72(m,1H), 6.72-6.70(m,1H),3.32-3.17(m,6H),2.77-2.75(m,2H),2.55-2.50(m,7H),2.27(s,3H).

[0143] Step 4: Synthesis of compound of formula (I)

[0144] To compound 1-5 (10 g) was added dimethyl sulfoxide (100 mL), followed by the addition of 2-(7-azobenzotriazole)-N,N,N,N-tetramethyluronium hexafluorophosphate (13.79 g), diisopropylethylamine (7.03 g), and ammonium bicarbonate (4.3 g). The mixture was stirred at 30° C. for 16 hours. The reaction solution was slowly poured into water (0.5 L), stirred at 25° C. for 16 hours, filtered, and the filter cake was collected to obtain a crude product. Water (100 mL) was added to the crude product, stirred at 25° C. for 16 hours, filtered, and the filter cake was collected. The residual solvent was dried with a stream of nitrogen to obtain the compound of formula (I). LCMS: m / z (ESI) = 551.2 [M+H] + . 1 H NMR(400MHz,DMSO-d6)δ:8.45(s,1H),8.32(s,1H),7.52-7.51(m,1H),7.34(s,2H),7.18-7.15( m,1H),6.72-6.68(m,1H),3.17-3.10(m,6H),2.75-2.71(m,2H),2.54-2.46(m,7H),2.23(s,3H).

[0145] Example 2: Preparation of Crystalline Form A of Compound (I)

[0146] 200 mg of the compound of formula (I) was weighed and added to a glass vial containing 3 mL of ethanol to form a suspension. After adding a magnet, the suspension sample was placed on a magnetic heating stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I). The XRPD spectrum is shown in Figure 1, the DSC spectrum is shown in Figure 2, and the TGA spectrum is shown in Figure 3.

[0147] Weigh 200 mg of the compound of formula (I) into a glass vial containing 3 mL of acetone to form a suspension. After adding a magnet, place the suspension sample on a magnetic stirrer and stir overnight at 60°C. The temperature is then lowered to room temperature and filtered. The solid sample is concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I).

[0148] Weigh 200 mg of the compound of formula (I) into a glass vial containing 3 mL of methanol to form a suspension. After adding a magnet, place the suspension sample on a magnetic stirrer and stir overnight at 60°C. The temperature is then lowered to room temperature and filtered. The solid sample is concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I).

[0149] 200 mg of the compound of formula (I) was weighed and added to a glass vial containing 1.5 mL of ethanol and 1.5 mL of water to form a suspension. After adding a magnet, the suspension sample was placed on a magnetic stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I).

[0150] 200 mg of the compound of formula (I) was weighed and added to a glass vial containing 1.5 mL of acetone and 1.5 mL of water to form a suspension. After adding a magnet, the suspension sample was placed on a magnetic stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I).

[0151] 200 mg of the compound of formula (I) was weighed and added to a glass vial containing 3 mL of ethyl acetate to form a suspension. After adding a magnet, the suspension sample was placed on a magnetic heating stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain Form A of the compound of formula (I). 1 H NMR(400MHz,D2O)δ:7.90(s,1H),7.30(d,J=8.8Hz,1H),7.14(d,J=3.2Hz,1H),7.00(dd,J=8.8,3.2Hz,1H), 3.74-3.77(m,2H),3.47-3.50(m,2H),2.99-3.15(m,4H),2.74-2.83(m,5H),2.51-2.59(m,2H),2.07(s,3H).

[0152] Example 3: Preparation of Crystalline Form B of Compound (II)

[0153] Approximately 50 mg of crystalline Form A of Compound (I) was weighed into 1.0 mL of ethanol and stirred at 50°C. 11.38 mg of succinic acid was diluted with 1 mL of ethanol solvent, and the diluted succinic acid solution was slowly added dropwise to the solvent. The mixture was stirred at 50°C for 20 hours, then cooled to 25°C and stirred for 4 days. After filtration, the mixture was dried at 50°C for approximately 18 hours to obtain crystalline Form B of Compound (II). The XRPD spectrum is shown in Figure 5, the DSC spectrum is shown in Figure 6, and the TGA spectrum is shown in Figure 7.

[0154] Weigh 45 mg of succinic acid into a glass vial containing 3 mL of ethanol and dissolve. Weigh 200 mg of the compound of formula (I) and add it to the above solution. Place the reaction solution on a magnetic stirrer and stir at 60°C overnight. Then cool it to room temperature and filter it. The solid sample is concentrated under reduced pressure using a vacuum pump to obtain the crystalline form B of the compound of formula (II).

[0155] Weigh 45 mg of succinic acid into a glass vial containing 3 mL of methanol and dissolve. Weigh 200 mg of the compound of formula (I) and add it to the above solution. Place the reaction solution on a magnetic stirrer and stir at 60°C overnight. Then cool it to room temperature and filter. The solid sample is concentrated under reduced pressure using a vacuum pump to obtain the crystalline form B of the compound of formula (II).

[0156] 45 mg of succinic acid was weighed and added to a glass vial containing 1.5 mL of methanol and 1.5 mL of water to dissolve. 200 mg of the compound of formula (I) was weighed and added to the above solution. The reaction solution was placed on a magnetic stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain crystalline Form B of compound of formula (II).

[0157] 45 mg of succinic acid was weighed and added to a glass vial containing 1.5 mL of ethanol and 1.5 mL of water to dissolve. 200 mg of the compound of formula (I) was weighed and added to the above solution. The reaction solution was placed on a magnetic stirrer and stirred at 60°C overnight. The temperature was then lowered to room temperature and filtered. The solid sample was concentrated under reduced pressure using a vacuum pump to obtain crystalline Form B of compound of formula (II).

[0158] Weigh 45 mg of succinic acid into a glass vial containing 3 mL of acetone and dissolve. Weigh 200 mg of the compound of formula (I) and add it to the above solution. Place the reaction mixture on a magnetic stirrer and stir at 60°C overnight. Then cool it to room temperature and filter it. The solid sample is concentrated under reduced pressure using a vacuum pump to obtain the crystalline form B of compound of formula (II). According to the NMR spectrum, m is 1.1. 1 H NMR(400MHz,D2O)δ:7.95(s,1H),7.35(d,J=9.2Hz,1H),7.18(d,J=2.4Hz,1H),7.04(dd,J=9.2,2.4Hz,1H),3. 80(m,2H),3.53(m,2H),3.01-3.20(m,4H),2.81-2.90(m,5H),2.58-2.67(m,2H),2.53(s,4.4H),2.18(s,3H).

[0159] Example 4: Preparation of Crystalline Form C of Compound (III)

[0160] Weigh 155 mg of the crude product from step 4 of Example 1, add water (1.5 mL), add concentrated hydrochloric acid (1.5 mL) to dissolve the crude product, add solid sodium hydroxide to adjust the pH to greater than 14, filter, collect the filter cake, add water (1 mL), stir at 25 ° C for 6 hours, filter, collect the filter cake, and bake in an oven at 50 ° C for 16 hours to obtain 150 mg, which was added to a 4.0 mL glass vial with 33.2 mg of fumaric acid and 2 mL of ethyl acetate to form a suspension. After adding a magnet, the suspension sample was placed on a magnetic heating stirrer (50 ° C) for testing, stirred at 50 ° C overnight, cooled, cooled to 25 ° C while stirring, filtered, and the filter cake was collected to obtain the crystalline form C of compound (III).

[0161] Weigh 520 mg of the crude product in step 4 of Example 1, add water (5.2 mL), add concentrated hydrochloric acid (5.2 mL) to dissolve the crude product, add solid sodium hydroxide to adjust the pH to greater than 14, filter, collect the filter cake, add water (3.7 mL), stir at 25 ° C for 6 hours, filter, collect the filter cake, and bake in an oven at 50 ° C for 16 hours to obtain 500 mg, which is added to a 40.0 mL glass vial, add 5 mL of a mixed solution of dichloromethane and methanol (dichloromethane: methanol = 2:1), add a magnetic stirrer at 50 ° C for 16 hours. After it was dissolved, 110.7 mg of fumaric acid was dissolved in 10 mL of a mixed solution of dichloromethane and methanol (dichloromethane: methanol = 2:1), and then added dropwise to a glass vial. The reaction solution sample was placed on a magnetic heating stirrer (50 ° C) for testing. After stirring at 50 ° C for 3 hours, the temperature was lowered, and after cooling to 20 ° C with stirring, it was filtered and the filter cake was collected to obtain a crystalline form of compound C of formula (III). According to the nuclear magnetic spectrum analysis, n was 1.0, the XRPD spectrum was shown in Figure 9, the DSC spectrum was shown in Figure 10, and the TGA spectrum was shown in Figure 11. 1 H NMR(400MHz,DMSO-d6)δ:8.48(s,1H),8.32(s,1H),7.55-7.50(m,1H),7.44(s,2H),7.22-7.15(m,1H),6.76-6.69(m,1 H),6.60(s,2H),3.23-3.16(m,4H),3.15-3.08(m,2H),2.79-2.70(m,2H),2.60-2.55(m,4H),2.54(s,3H),2.30(s,3H).

[0162] Example 5: Preparation of Crystalline Form D of Compound (IV)

[0163] Weigh approximately 50 mg of the crystalline form A of compound of formula (I) into 1.0 mL of ethanol and stir at 50°C. Weigh 15.28 mg of benzenesulfonic acid in 1 mL of ethanol solvent, and slowly add the diluted benzenesulfonic acid solution dropwise to the above solvent. Stir at 50°C for 20 hours, then cool to 25°C and stir for 4 days. After filtering, dry at 50°C for about 18 hours to obtain the crystalline form D of compound of formula (IV). According to the nuclear magnetic resonance spectrum analysis, p is 0.9, the XRPD spectrum is shown in Figure 13, the DSC spectrum is shown in Figure 14, and the TGA spectrum is shown in Figure 15. 1 H NMR(400MHz, DMSO-d6)δ:9.37-9.69(m,0.9H),8.59(s,1H),8.33(s,1H),7.56-7.65(m,1.8H),7.54(d,J=3.2Hz,1H),7.44-7.56(m,2H),7.27-7 .36(m,2.7H),7.24(d,J=8.4Hz,1H),6.80(dd,J=8.4,3.2Hz,1H),3.40- 3.96(m,4H),2.92-3.26(m,6H),2.86(s,3H),2.74(m,2H),2.54(s,3H).

[0164] Example 6: Crystal form screening experiment

[0165] 6.1 Suspension Crystallization

[0166] The suspension crystallization process involves weighing a certain amount of Form A of Compound (I), adding a certain amount of solvent, maintaining the system in a suspended state with stirring at a certain temperature, and then filtering the solids for analysis after a period of time. Specific conditions are shown in Table 6.

[0167] Table 6. Suspension crystallization

[0168] 6.2 Cooling crystallization

[0169] The cooling crystallization process involves dissolving a certain amount of Form A of Compound (I) in a certain amount of solvent at high temperature, stirring at high temperature for a period of time, and then cooling the solution to a lower temperature at a certain rate. If solid precipitates after cooling to a lower temperature, the solid is filtered and analyzed. Specific conditions are shown in Table 7.

[0170] Table 7. Cooling crystallization

[0171] 6.3 Dissolution and crystallization

[0172] The solvent crystallization process involves dissolving a certain amount of crystalline form A of Compound (I) in a positive solvent to obtain a solution of the active pharmaceutical ingredient. This solution is then slowly added to the antisolvent at a specific temperature. Any solid precipitates are filtered and analyzed. Specific conditions are shown in Table 8.

[0173] Table 8. Dissolution crystallization

[0174] Experimental conclusion: The crystal form A of compound of formula (I) has certain stability in different solvents and temperatures.

[0175] Example 7: Hygroscopicity study of the crystal form A of compound of formula (I)

[0176] Experimental Materials:

[0177] SMS DVS Intrinsic Dynamic Vapor Sorption Analyzer

[0178] Experimental methods:

[0179] 10-30 mg of the crystalline form A of the compound of formula (I) was placed in a DVS sample tray for testing.

[0180] Experimental results:

[0181] The DVS spectrum of the crystal form A of the compound of formula (I) is shown in FIG4 . When the humidity rises to 80%, ΔW=0.1671%.

[0182] Experimental conclusion:

[0183] The weight gain of the crystal form A of the compound of formula (I) at 25° C. and 80% RH was 0.1671%, and the sample was not hygroscopic.

[0184] Example 8: Hygroscopicity Study of Crystal Form B of Compound (II)

[0185] Experimental Materials:

[0186] SMS DVS Intrinsic Dynamic Vapor Sorption Analyzer

[0187] Experimental methods:

[0188] 10-30 mg of the crystalline form B of compound of formula (II) was placed in a DVS sample tray for testing.

[0189] Experimental results:

[0190] The DVS spectrum of the crystal form B of compound of formula (II) is shown in FIG8 . When the humidity rises to 80%, ΔW=2.078%.

[0191] Experimental conclusion:

[0192] The weight gain of the crystal form B of the compound of formula (II) at 25° C. and 80% RH is 2.078%, indicating that it is hygroscopic.

[0193] Example 9: Hygroscopicity Study of Crystal Form C of Compound (III)

[0194] Experimental Materials:

[0195] SMS DVS Intrinsic Dynamic Vapor Sorption Analyzer

[0196] Experimental methods:

[0197] 10-30 mg of the crystalline form C of the compound of formula (III) was placed in a DVS sample tray for testing.

[0198] Experimental results:

[0199] The DVS spectrum of the crystal form C of the compound of formula (III) is shown in FIG12 . When the humidity rises to 80%, ΔW=2.919%.

[0200] Experimental conclusion:

[0201] The weight gain of the crystal form C of the compound of formula (III) at 25° C. and 80% RH is 2.919%, indicating that it is hygroscopic.

[0202] Example 10: Solid Stability Test of Compound A (Formula (I)) and Compound B (Formula (II))

[0203] Purpose of the experiment:

[0204] According to the "Guidelines for Stability Testing of APIs and Pharmaceutical Products" (Chinese Pharmacopoeia 2020 Edition, Part IV, General Rules 9001), the stability of the crystalline form A of compound (I) and the crystalline form B of compound (II) under high temperature and high humidity (40°C / 75% RH, open) (60°C / 75% RH, open) conditions was investigated. Experimental procedures:

[0205] Weigh 10-30 mg of Form A of Formula (I) and Form B of Formula (II) and place them in a thin layer at the bottom of a glass sample bottle. The samples were left uncovered to ensure adequate contact with ambient air. Samples stored under different conditions were sampled and tested (XRPD) on days 10, 30, and 60. The results were compared with the initial test results on day 0. The test results are shown in Table 9:

[0206] Table 9. Solid stability test results of the crystal form of compound A of formula (I) and the crystal form of compound B of formula (II)

[0207] Experimental conclusion: The crystal form A of compound of formula (I) and the crystal form B of compound of formula (II) have good stability under high temperature and high humidity conditions.

[0208] Test Example 1: Pharmacokinetic study of oral administration of the test compound in male beagle dogs

[0209] Purpose of the experiment:

[0210] This study was designed to investigate the pharmacokinetics of the test compound in the plasma of male beagle dogs after oral administration.

[0211] Experimental operation:

[0212] Oral administration group: Weigh an appropriate amount of test compound (calculated as free form) and dissolve it in a 0.5% MC aqueous solution. Vortex and sonicate for 10 minutes until the compound becomes a milky white, homogeneous suspension to prepare a 1.0 mg / mL suspension. Male beagle dogs weighing approximately 11 kg were orally administered with the test compound. Samples were collected at 0.083, 0.25, 0.5, 1, 2, 4, 6, 8, and 24 hours.

[0213] At each time point, approximately 1 mL of whole blood was collected from a forelimb vein to prepare plasma for concentration determination by high-performance liquid chromatography-tandem mass spectrometry (LC-MS / MS). Plasma concentrations were analyzed using a non-compartmental model using WinNonlin 8.2.0 (Pharsight, Mountain View, CA) pharmacokinetic software, and pharmacokinetic parameters were calculated using the linear-log trapezoidal method. The experimental results are shown in Table 10:

[0214] Table 10. Pharmacokinetic study results of crystal forms A, B, and C

[0215] Experimental conclusion: Crystalline form A of compound (I), crystalline form B of compound (II) and crystalline form C of compound (III) were all well absorbed in male beagle dogs after oral administration.

[0216] Test Example 2: In vitro evaluation of PLK1 kinase activity

[0217] use 33 IC was determined by P isotope-labeled kinase activity assay (Reaction Biology Corp). 50 The inhibitory ability of the test compound on human PLK1 protein kinase was evaluated by PCR.

[0218] Buffer conditions: 20 mM HEPES (pH 7.5), 10 mM MgCl2, 1 mM EGTA, 0.01% Brij35, 0.02 mg / mL BSA, 0.1 mM Na3VO4, 2 mM DTT, 1% DMSO

[0219] Experimental steps: At room temperature, the test compound was dissolved in DMSO to prepare a 10mM solution for use. The substrate Casein was dissolved in a freshly prepared buffer (final concentration 20μM), and the PLK1 kinase to be tested (final concentration 12nM) was added thereto and mixed evenly. The DMSO-dissolved test compound stock solution was added to the above-mentioned mixed reaction solution according to the set final concentration gradient (the highest final concentration was 1μM, 3-fold dilution, 10 gradients) using the acoustic pipetting system Echo 550. After incubation at room temperature for 20 minutes, the mixture was added. 33 After incubation at room temperature for 120 minutes with P-ATP (final concentration 0.01 μCi / μL), the reaction solution was spotted onto P81 ion exchange filter paper (Whatman #3698-915). After repeated washing with 0.75% phosphoric acid solution, the level of radioactive phosphorylated substrate remaining on the filter paper was determined. % kinase activity = kinase activity of test compound / kinase activity of blank (DMSO) × 100%. Curve fitting was performed using Prism 4 software (GraphPad) to obtain the IC 50 The experimental results are shown in Table 11.

[0220] Table 11. Results of in vitro PLK1 kinase activity screening test of the compounds of the present invention

[0221] Experimental conclusion: Crystal form A of compound of formula (I) exhibits good inhibitory activity against PLK1.

Claims

1. Succinate, fumarate, benzenesulfonate, sulfate, phosphate, maleate, L-tartrate, methanesulfonate, L-malate, hydrochloride, citrate and L-aspartate salts of the compound of formula (I):

2. The salt of the compound according to claim 1, which is selected from: in, m, n, p, q, r, s, t, u, v, w, x and y are independently selected from 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 and 2.0, respectively.

3. The salt of claim 2, wherein m, n, p, q, r, s, t, u, v, w, x and y are each independently selected from 1.

0.

4. Crystal form A of the compound of formula (I), characterized in that Its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 12.661±0.200°, 19.637±0.200°, 5. The crystal form A according to claim 4, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 13.479±0.200°, 19.637±0.200°, 23.281±0.200°, and 24.892±0.200°.

6. The crystal form A according to claim 5, whose X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.305±0.200°, 9.140±0.200°, 9.681±0.200°, 12.661±0.200°, 13.479±0.200°, 14.139±0.200°, 16.523±0.200°, 18.385±0.200°, 19.637±0.200°, 21.161±0.200°, 23.281±0.200°, and 24.892±0.200°.

7. The crystal form A according to claim 6, whose X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.305°, 9.140°, 9.681°, 11.138°, 12.661°, 13.479°, 14.139°, 15.175°, 16.523°, 18.385°, 18.710°, 19.094°, 19.637°, 19.904°, 20.692°, 21.161°, 21.915°, 22.159°, 23.281°, 23.630°, 24.892°, 25.491°, 26.582°, and 32.389°.

8. The crystal form A according to any one of claims 4 to 7, whose XRPD pattern is substantially as shown in Figure 1. 9 . The crystal form A according to claim 4 , wherein the differential scanning calorimetry curve thereof has an endothermic peak starting value at 222.64±3.0° C.

10. The crystal form A according to claim 9, whose DSC spectrum is shown in Figure 2.

11. The crystal form A according to any one of claims 4 to 7, wherein the thermogravimetric analysis curve thereof shows a weight loss of 1.220% at 242±3°C.

12. The crystal form A according to claim 11, whose TGA spectrum is shown in Figure 3.

13. Form B of the compound of formula (II), wherein m is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.855±0.200°, 17.861±0.200°, 19.915±0.200°, 24.154±0.200°, 14. The crystal form B according to claim 13, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 13.855±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 24.154±0.200°, and 27.518±0.200°.

15. The crystal form B according to claim 14, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.333±0.200°, 11.034±0.200°, 13.855±0.200°, 14.350°±0.200°, 16.116±0.200°, 17.861±0.200°, 18.764±0.200°, 19.915±0.200°, 20.651±0.200°, 21.157±0.200°, 24.154±0.200°, and 27.518±0.200°.

16. The crystal form B according to claim 15, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 7.333°, 11.034°, 12.635°, 13.534°, 13.855°, 14.350°, 16.116°, 17.483°, 17.861°, 18.764°, 19.658°, 19.915°, 20.651°, 21.157°, 23.449°, 23.806°, 24.154°, 24.702°, 26.884°, 27.518°, and 31.071°.

17. The crystal form B according to any one of claims 13 to 16, which has an XRPD pattern substantially as shown in Figure 5.

18. The crystal form B according to any one of claims 13 to 16, wherein the differential scanning calorimetry curve thereof has an endothermic peak onset at 193.63±3.0°C.

19. The crystal form B according to claim 18, whose DSC spectrum is shown in Figure 6.

20. The crystal form B according to any one of claims 13 to 16, wherein the thermogravimetric analysis curve thereof shows a weight loss of 0.867% at 92±3°C.

21. The crystal form B according to claim 20, whose TGA spectrum is shown in Figure 7.

22. Form C of the compound of formula (III), wherein n is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 13.637±0.200°, 14.138±0.200°, 17.076±0.200°, 24.866±0.200°, 23. The crystal form C according to claim 22, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 11.412±0.200°, 13.637±0.200°, 14.138±0.200°, 17.076±0.200°, 19.310±0.200°, 23.654±0.200°, 24.214±0.200°, and 24.866±0.200°.

24. The crystalline form C according to claim 23, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 11.412±0.200°, 13.637±0.200°, 14.138±0.200°, 15.555±0.200°, 17.076±0.200°, 18.016±0.200°, 18.907±0.200°, 19.310±0.200°, 20.811±0.200°, 23.654±0.200°, 24.214±0.200°, and 24.866±0.200°.

25. The crystal form C according to claim 24, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 5.677°, 7.086°, 11.412°, 11.627°, 13.200°, 13.429°, 13.637°, 14.138°, 14.499°, 15.167°, 15.555°, 15.763°, 17.076°, 17.272°, 18. 016°, 18.171°, 18.614°, 18.907°, 19.310°, 19.656°, 20.016°, 20.811°, 21.765°, 22.748°, 23.443°, 23.654°, 23.880°, 24.214°, 24.577°, 24.866°, 25.987°, 26.493°, 27.011°, 27.537°.

26. The crystal form C according to any one of claims 22 to 25, which has an XRPD pattern substantially as shown in Figure 9.

27. The crystal form C according to any one of claims 22 to 25, wherein its differential scanning calorimetry curve has an endothermic peak onset at 237.14±3.0°C.

28. The crystal form C according to claim 27, whose DSC spectrum is shown in Figure 10.

29. The crystal form C according to any one of claims 22 to 25, wherein the thermogravimetric analysis curve thereof shows a weight loss of 0.469% at 100±3°C.

30. The crystal form C according to claim 29, whose TGA spectrum is shown in Figure 11.

31. Form D of the compound of formula (IV), wherein p is selected from 0.8, 0.9, 1.0, 1.1 and 1.2, and its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 16.420±0.200°, 18.965±0.200°, 32. The crystalline form D according to claim 31, wherein its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 10.922±0.200°, 13.238±0.200°, 16.420±0.200°, 18.965±0.200°, 20.400±0.200°, and 24.069±0.200°.

33. The crystalline Form D according to claim 32, wherein the X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.859±0.200°, 8.784±0.200°, 10.922±0.200°, 11.644±0.200°, 13.238±0.200°, 16.420±0.200°, 17.596±0.200°, 18.965±0.200°, 19.390±0.200°, 20.400±0.200°, 21.416±0.200°, and 24.069±0.200°.

34. The crystalline Form D according to claim 33, wherein the X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ angles: 6.859°, 8.784°, 10.922°, 11.644°, 13.238°, 13.741°, 16.420°, 16.720°, 17.596°, 17.930°, 18.965°, 19.390°, 20.400°, 21.416°, 22.630°, 23.473°, 24.069°, 24.832°, 26.587°, and 27.661°.

35. The crystal form D according to any one of claims 31 to 34, which has an XRPD pattern substantially as shown in Figure 13.

36. The crystal form D according to any one of claims 31 to 34, wherein the differential scanning calorimetry curve thereof has an endothermic peak onset at 240.70±3.0°C.

37. The crystal form D according to claim 36, whose DSC spectrum is shown in Figure 14.

38. The crystal form D according to any one of claims 31 to 34, wherein the thermogravimetric analysis curve thereof shows a weight loss of 0.295% at 120±3°C.

39. The crystal form D according to claim 38, whose TGA spectrum is shown in Figure 15.

40. Use of the salt form according to any one of claims 1 to 3, the crystal form A according to any one of claims 4 to 12, the crystal form B according to any one of claims 13 to 21, the crystal form C according to any one of claims 22 to 30, or the crystal form D according to any one of claims 31 to 39 in the preparation of a drug for treating solid tumors.

41. The use according to claim 40, characterized in that The drug for treating solid tumors is a drug for treating colorectal cancer.